HUBUNGAN ANTARA INTAKE ZAT GIZI MAKRO, ZAT BESI, DAN VITAMIN C DENGAN KADAR HEMOGLOBIN SISWI SMA DI KECAMATAN KEBOMAS - Rahma Fidania Dwik Nuraini; Eka Srirahayu Ariestiningsih; Desty Muzarofatus Sholikhah (Ghidza Media Jurnal, 2022)
Anemia is a condition where the number of erythrocytes or the amount of hemoglobin is below the normal value standard, which is more at risk for adolescent girls. The purpose of this study was to analyze the relationship between intake of macronutrients, iron, and vitamin C with hemoglobin levels of high school students in Kebomas District. This research method uses analytic observational research. The population as many as 115 high school students in Kebomas sub-district were taken using cluster random sampling technique. Data was collected using a food recall, food photo books, digital scales, digital Hb, and a form of measuring Hb levels. Data analysis used Kendall's tau-b and rank concordance. The results showed that there was a significant relationship between intake of macronutrients ((protein (Sig=0.004)), fat (Sig=0.043), carbohydrates (Sig=0.047), iron (Sig=0.000) and vitamin C (Sig= 0.028) with hemoglobin levels.The conclusion of this study is that there is a relationship between intake of macronutrients, iron, and vitamin C with hemoglobin levels in high school students. So it is necessary to provide nutrition education and routine iron tablets as an effort to prevent anemia in adolescent girls.